Characterization of Physiological Responses and Deciphering Differential Expression of Heat stress Responsive Candidate Genes in Rice under High Temperature - Lohitha, Poola; H, Patil Arun; Chandel, Girish (International Journal of Bio-resource and Stress Management, 2020)
With increasing global temperature (by 1.5-4.8 °C by 2100) and its negative impact on crop productivity of major food crops including rice (by 41% by 21st century), a study was undertaken to assess the genes involved in maintaining crop metabolism and sustenance under high temperature. Rice, most important staple food crop feeds around 3 billion people, hence producing improved heat tolerant varieties is necessary. High temperatures produce new group proteins called ‘Heat Shock Proteins (HSPs), whose transcription is guarded by heat shock transcription factors (Hsfs). HSPs refold proteins maintaining functional conformation, aiding in host-defence mechanisms. The aim of this research was to assess physiological and biochemical changes and to analyze key genes expressed due to high temperature exposure. Expression profiling of five heat responsive genes (OsHSP26.7, OsHSP16.9, OsHSP-DnaJ, OsHSP18 and 60Kda-chaperon), in rice showed up-regulation. Pollen fertility, spikelet fertility, photosynthetic pigments like chlorophyll a, chlorophyll b and total chlorophyll content decreased under heat stress while membrane stability index, proline and Malondialdehyde was increased. This study suggested OsHSP26.7 as most responsive gene under stress and rice genotypes RRF-127, Annada with heat tolerant adaptive mechanisms and better performance under high temperatures. These findings were observed to be in correlation with the phenological, biochemical and expression analysis studies carried out with five different heat responsive genes. This can be taken as a base for heat tolerance response of rice crop, which may be useful for further validation studies of the candidate genes responsive for heat stress in rice.